A phylogenetic approach to understanding dinosaur egg diversity and the evolution of reproductive traits within Dinosauria - Barta, Daniel Eric (Montana State University - Bozeman, College of Letters & Science, 2014)
Fossil eggs provide a unique source of information about the reproductive biology of extinct vertebrates. Dinosaur eggshell, eggs, and clutches are of particular interest because of their great diversity in size, shape, microstructure, and clutch configurations relative to extant egg-laying taxa. In order to provide an explicity phylogenetic framework within which to investigate this diversity and to form more rigorous hypotheses about the identities of egg types that lack associations with adult or embryonic remains, cladistic analyses of 36 oological characters were peformed for 48 egg types. This study aimed to achieve a broader ootaxonomic coverage than previous studies, including pterosaur eggs for the first time in an outgroup with crocodilians and turtles in order to better polarize character states. The first set of analyses did not restrict the positions of ingroup eggs; however, the second utilized a backbone constraint to restrict the positions of taxonomically identified eggs on the tree, allowing unidentified ootaxa to fall out freely relative to a stable framework of relationships based on consensus osteological phylogenies. The results of all analyses reveal Chinese spheroolithids and Mongolian dendroolithids grouping together to the exclusion of other members of those oofamilies (and alongside therizinosauroid eggs) suggesting that Spheroolithidae and Dendroolithidae are polyphyletic. The constrained analysis additionally reveals Ovaloolithus and Cairanoolithus as the only egg types unresolved at the base of Dinosauria on an Adams consensus tree, suggesting that they could belong to either saurischians or ornithischians. All other taxonomically unidentified ootaxa fall out as saurischians, suggesting that the lack of ornithischian eggs in the fossil record is the result of real biases acting against their preservation, and is not simply an artifact of a lack of preserved embryos whereby they might be identified. Major transitions in dinosaur eggshell evolution include the evolution of a second structural layer of calcite within Avetheropoda, and a reversal to a single-layered condition within Therizinosauroidea. As in previous studies, a stepwise accumulation of avian-like character states within theropods precedes the appearance of extant avian clades. This study highlights the need for ongoing application of cladistic and related principles to the study of fossil eggs.
Keywords: Dinosaurs; Eggs; Reproduction; Phylogeny